Unresolved Grief and the Pull of the Dead in Joyce’s ‘Eveline’: An Interpretation Using Attachment Theory - Linda Horsnell (Janeway JS, 2020)
This paper uses Attachment Theory as a frame of reference to critically analyse James Joyce’s representation of the eponymous character Eveline in Dubliners. By reference to the work of Alexander Shand, it is possible to highlight the correlative relationship between creative writing and the theory of grief espoused by attachment theorist John Bowlby. Joyce’s understanding of human behaviour and the sociological, domestic and psychological information contained within his work leave it particularly open to critical analysis using such methodology. I will show how attachment theory offers an alternative reading to those based on Freudian and Lacanian paradigms.